An individualized approach to teaching adults with autism to successfully navigate job interviews via remote instruction. Issue 2 (9th February 2023) - Kahng, SungWoo; Butler, Courtney; Kronfli, Faris R.; Zaki‐Scarpa, Christeen; Boragi, Brianna; Scott, Joseph
Abstract: Adults with autism spectrum disorder (ASD) experience challenges securing employment, which may partially explain overall underemployment or unemployment in this population. One of the first steps to obtaining employment is participating in a job interview. However, social communication deficits may interfere with an individual with ASD's participation in a job interview. The current study evaluated the use of behavioral skills training delivered via remote instruction to teach interview skills to seven adults with ASD. Results showed overall improvement during interviews as well as posttraining tests with a career development expert. These data suggest that an individualized approach to teaching may be an effective strategy to help adults with ASD successfully navigate job interviews.